2018
DOI: 10.1186/s12870-018-1326-1
|View full text |Cite
|
Sign up to set email alerts
|

A biolistic method for high-throughput production of transgenic wheat plants with single gene insertions

Abstract: BackgroundThe relatively low efficiency of biolistic transformation and subsequent integration of multiple copies of the introduced gene/s significantly complicate the genetic modification of wheat (Triticum aestivum) and other plant species. One of the key factors contributing to the reproducibility of this method is the uniformity of the DNA/gold suspension, which is dependent on the coating procedure employed. It was also shown recently that the relative frequency of single copy transgene inserts could be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 42 publications
(50 reference statements)
0
25
0
Order By: Relevance
“…For stable transformation of wheat (T. aestivum L. cv. Bobwhite), the pTdGL7 construct was cotransformed together with a plant selectable marker cassette (Ubi-hpt-nos) into wheat using microprojectile bombardment as described in (Kovalchuk et al 2009;Ismagul et al 2018). The integration of promoter-GUS fusions in transgenic plants was confirmed by PCR using primers derived from promoter and GUS (uidA) sequences.…”
Section: Plant Transformation and Analysesmentioning
confidence: 99%
“…For stable transformation of wheat (T. aestivum L. cv. Bobwhite), the pTdGL7 construct was cotransformed together with a plant selectable marker cassette (Ubi-hpt-nos) into wheat using microprojectile bombardment as described in (Kovalchuk et al 2009;Ismagul et al 2018). The integration of promoter-GUS fusions in transgenic plants was confirmed by PCR using primers derived from promoter and GUS (uidA) sequences.…”
Section: Plant Transformation and Analysesmentioning
confidence: 99%
“…There is general agreement that the transgene segregation could be more predictable in the case of a single insert or a low number of insertions. We believe that some methodological approaches, such as the use of dephosphorylated gene cassette [ 41 ] or linear form of the construct [ 48 ], and the PEG/Mg2+ coating procedure [ 49 ] will be useful for combination with the method presented here to increase the number of transgenic events with simple integration patterns.…”
Section: Discussionmentioning
confidence: 99%
“…However, the quality of the integration events is usually lower than Agrobacterium-mediated transformation and rarely results in clean single-copy integration of the DNA construct [104,105]. Both circular and linear DNA can be introduced into plant cells by particle bombardment, and the co-delivery of different DNA fragments or plasmids is quite efficient because they can be coated onto the same microparticles [121,122]. A recent study in wheat demonstrated the ZFN-mediated precise editing of the three homoeologous ALS genes following bombardment with the ZFN construct and a short dsDNA donor with compatible overhangs [76].…”
Section: Delivery Methodsmentioning
confidence: 99%